Perancangan Sistem Kontrol Pendingin Udara Otomatis Berbasis Suhu Ruangan Menggunakan Arduino - Mhd Galih Khairi; Muhammad Irfan Gurning; Mhd. Furqan (Jurnal Ilmu Komputer dan Sistem Informasi, 2024)
Air conditioning has become essential in the modern era, with nearly everyone worldwide owning an air conditioner in their homes. Its presence is crucial given the increasingly hot weather conditions due to global warming. However, we often forget to turn off the air conditioner, resulting in energy waste and potential damage to the device. Therefore, this writing aims to address these issues through the development of an automatic system using Arduino Nano, programmed in the C language, to regulate the operation of the air conditioner based on room temperature. This way, users do not need to bother manually turning the air conditioner on or off using a remote control or buttons.